2016
DOI: 10.3324/haematol.2016.154070
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum free light chain assay in the detection of early relapse and prediction of prognosis after relapse in multiple myeloma patients treated upfront with novel agents

Abstract: Role of serum free light chain assay in the detection of early relapse and prediction of prognosis after relapse in multiple myeloma patients treated upfront with novel agentsCI: confidence interval; sFLCR: serum free light chains ratio; 2 nd TTP: time to second progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
2
13
1
Order By: Relevance
“…These data are in agreement with 2016 IMWG consensus, that has maintained, among standard response criteria, the value of "stringent CR" in patients with immune-fixation negative response (Kumar et al, 2016), though this has been recently questioned (Mart ınez-L opez et al, 2015). Interestingly, Tacchetti et al (2017) recently confirmed a relationship between relapse defined by increasing levels of FLC and shorter time to second-line therapy, risk of second progression and risk of death as compared to a relapse with increase in M-protein only.…”
mentioning
confidence: 71%
“…These data are in agreement with 2016 IMWG consensus, that has maintained, among standard response criteria, the value of "stringent CR" in patients with immune-fixation negative response (Kumar et al, 2016), though this has been recently questioned (Mart ınez-L opez et al, 2015). Interestingly, Tacchetti et al (2017) recently confirmed a relationship between relapse defined by increasing levels of FLC and shorter time to second-line therapy, risk of second progression and risk of death as compared to a relapse with increase in M-protein only.…”
mentioning
confidence: 71%
“…As expected, our analysis demonstrates that during the course of first-line therapy, there is an increasing percentage of patients achieving FLCr normalization with a maximum after consolidation. Tacchetti et al showed similar rates of patients achieving a normal FLCr after first-line treatment with a bortezomib-based regime [ 32 ]. In contrast, in a Japanese study, only 41% of the patients reached FLCr normalization after a novel agent-containing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although the IMWG response criteria are widely used in every line of therapy, there are no clinical data that confirm the validity of this evaluation from the second line of therapy onwards. Moreover, to date there have been several studies that have validated the usefulness of serial FLC measurements with rFLC and differential FLC (dFLC) in MM population, especially in OS, NS, and LC MM with poor prognosis, 11,12,[15][16][17][18] but currently there are no prospective studies performed in the era of novel agents.…”
Section: Discussionmentioning
confidence: 99%